What can Urban Waters teach us? Prospects of action in the metropolitan region of Rio de Janeiro - Araujo , Eloisa Carvalho de (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The work presented here is based on a continuous research process and aims to work on the environment from the understanding of the relationship of cities in the metropolitan region of Rio de Janeiro, with its main urban rivers and to reflect on alternative solutions to the problems found. The challenge presented, in the ongoing research, from the experience of the Ubatiba River, in the city of Maricá, seeks to identify distortions and seek to make the reflections, within the principles of sustainability, produce effects on planning, design and management practices of the city, its urban waters. For this purpose, this investigation also intends to rely on the understanding and understanding of the existing legal provisions that guide the development of the target cities, committing, by bringing to the debate some reflections, based on theoretical-practical investigations, not to exhaust the theme, but rather to situate it as relevant in the face of the reality of the problems that surround cities, especially Brazilian cities, in contemporary times.